Contributions for experimental and numerical characterization of the structural behaviour of stone arch bridges - C. Costa (2019)
This paper reports on methodologies for experimental and numerical characterization of the structural behaviour of stone arch bridges based on several studies of bridges existing in the Portuguese network. The main contributions are focused on results of technical inspections, experimental testing and numerical simulation. The objectives and achievements of the selected case studies are presented and discussed aiming for a general overview of the methodologies carried out to assess the bridge structural behaviour.